Is Planckian Discreteness Observable in Cosmology? - Bengochea, Gabriel Roman (2025)
A Planck scale inflationary era, in a quantum gravity theory predicting discreteness of quantum geometry at the fundamental scale, produces the scale invariant spectrum of inhomogeneities with a very small tensor-to-scalar ratio of perturbations and a hot big bang leading to a natural dark matter genesis scenario. Here, we evoke the possibility that some of the major puzzles in cosmology would have an explanation rooted in quantum gravity.